EFEKTIVITAS PEMEKARAN KECAMATAN DALAM MENINGKATKAN PEMBANGUNAN Studi Deskriptif Kualitatif di Kecamatan Insana Tengah Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Agustinus Naisaban; Mutia Rahmah (Fakultas Politik Pemerintahan IPDN, 2019)
Efectiveness of Sub-District Expansion in Improving Development. This study aims to determine the effectiveness of sub-district expansion in increasing development in Central Insana District, North Central Timor Regency, East Nusa Tenggara Province. Expansion of Subdistricts in Central Insana Subdistrict has been regulated in the Regional Regulation of North Central Timor Number 8 of 2007 with the aim of equitable development, optimizing the implementation of governance and shortening the range of control of empowerment and community development services and accommodating aspirations that develop in the community. After 12 years running, the District Expansion policy has not shown a positive impact on the community, especially the development aspect. This study uses descriptive qualitative research methods. Data collection techniques used were interviews, documentation and observation. The results showed that the policy of sub-district expansion in increasing development in Central Insana District was not yet effective, because of the weak role of the sub-district in providing services to the community. Budget limitations, inadequate transportation facilities and infrastructure and damaged road conditions, and a lack of active community participation in supporting the implementation of development in Central Insana Subdistrict, are classic reasons. Keywords: effectiveness, expansion, development